Efforts to Increase Students Learning Motivation Through Physical Fitness Games in Physical - Mochamad Afif Baihaqi; Ridwan, Mochamad; Juheri (Jurnal Pendidikan Jasmani (JPJ), 2023)
In learning physical education, the most basic thing is student motivation to take part in learning. The focus of the problem in this PTK is an effort to increase student motivation through physical fitness games for class VII F students of SMP Negeri 1 Bangsal, which are not as expected. The purpose of this research is to increase the learning motivation of class VII F students through a game approach. This research is a classroom action research that emerges from the learning process. The subjects of this study were 32 students in class VII F of SMP Negeri 1 Bangsal. The research instrument was a motivational questionnaire to find out how much students were motivated. The indicator for the success of this classroom action research was a significant increase in student learning motivation. The results of this study show that learning physical education with a game approach to physical fitness is evident that most students have high motivation of 51.3% and most have a fitness level in the moderate category of 43.3%. In learning physical fitness activities through games has increased.